PENILAIAN PORTOFOLIO: SUATU MODEL EVALUASI HASIL BELAJAR DALAM PEMBELAJARAN BERDASARKAN TEORI BELAJAR EKSPERIENSIAL - Ismaniati, Christina (MAJALAH ILMIAH PEMBELAJARAN, 2006)
Through learning experiences students are expected to develop and achieve not only cognitive goals but also affective and psychomotor as well. So, as the environment of learning, schools must to maintain and facilitate students to reach the three goals by a lot of experiences based on experiential learning theory. The assessment and evaluation of the learning process is also addressed parallel with that theory, and the important one is Portfolio Assessment. But in fact, and so far, the learning experiences given to students especially in the classroom, is reduced by isolated information telling from teacher to students. Hence, the objective or paper pencil test is the best choice types of test think by the teachers rather than the others type more authentic. It is weak and unsupported. This article describes portfolio as one types of assessment models teachers may choose to assess students learning based on Experiential Learning Theory, included how to prepare and apply it in our classroom teaching and learning.